Upaya Peningkatan Gizi Anak melalui Penyuluhan Konsumsi Protein Hewani dan Demonstrasi Pembuatan Sosis Hati Ayam - Khalida Dalimunthe, Nathasa; Khoeirunnisa, Tiara Kurnia; Dalimunthe, Nindytia Puspitasari; Aulia, Cindy; Khoirunisa, Aprilia (Forum Kerjasama Pendidikan Tinggi, 2025)
The health condition of toddlers in the Kedaton Community Health Center working area in January 2025 in Sukamenanti Baru Village showed that the coverage of toddlers who experienced weight gain was only 85% so it has not reached the target. Chicken liver is a food ingredient that is easily available and inexpensive. However, children tend to dislike consuming chicken liver directly, so there is a need for innovation in forms that suit children's tastes, such as being processed into other, more attractive products. This community service aims to provide understanding to mothers regarding the importance of consuming animal foods and empowering KWT Melati Jaya through training in processing chicken liver sausages as a nutritious food solution that is affordable and liked by children. The activity was carried out July-August 2025 at the Al-Fitrah Mosque, Sukamenanti Baru, Kedaton, Bandar Lampung. Counseling activities were carried out using lecture methods and leaflet media, while the activity of making chicken liver sausages was carried out using a direct demonstration method for KWT mothers. There was a significant increase in mothers' knowledge about animal protein (p = 0.000) (average pre-test score of 78.8 to post-test 93.3). All groups were quite successful in making chicken liver sausages, resulting in a product they enjoyed (good taste, minimal odor). This sausage has the potential to provide a nutritional solution for toddlers and a business opportunity with a long shelf life.